Geoekonomia jako paradygmat zarządzania rozwojem – przykład Chin - Grosse, Tomasz Grzegorz (Journal of Public Governance, 2014)
The paper attempts to determine whether geoeconomics can be considered as a new paradigm of public management. In geoeconomics, development policy is based on geopolitical objectives related to strengthening the capacities and the role of the state (or regional grouping) in the international arena. Therefore, geopolitical motivation predominates and it replaces other goals of development policy, for example relating to the democratic needs of equal opportunities, social justice, or the efficiency of public institutions. As an example, the author discusses 30 years of development management in the PRC. The paper presents specific characteristics of the Chinese management resulting from its geoeconomic strategy.